2021
DOI: 10.1126/sciadv.abg0221
|View full text |Cite
|
Sign up to set email alerts
|

Genomic evidence for the Chinese mountain cat as a wildcat conspecific ( Felis silvestris bieti ) and its introgression to domestic cats

Abstract: The Qinghai-Tibet Plateau endemic Chinese mountain cat has a controversial taxonomic status, whether it is a true species or a wildcat (Felis silvestris) subspecies and whether it has contributed to cat (F. s. catus) domestication in East Asia. Here, we sampled F. silvestris lineages across China and sequenced 51 nuclear genomes, 55 mitogenomes, and multilocus regions from 270 modern or museum specimens. Genome-wide analyses classified the Chinese mountain cat as a wildcat conspecific F. s. bieti, which was no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 60 publications
3
12
0
Order By: Relevance
“…The persistence of these ancient and diverged lineages in the Indian subcontinent may be due in part to the region’s unique topography and paleoenvironmental history. Similar patterns of locally divergent lineages have been observed in Trans-Himalayan red pandas ( Hu et al 2020 ) and Chinese mountain cats ( Yu et al 2021 ). Together, these findings point to the importance of the Indian subcontinent and Trans-Himalayan region as refugia during the Pleistocene ( Sharma et al 2004 ; Costa 2017 ) that enabled the persistence of divergent lineages.…”
Section: Discussionsupporting
confidence: 71%
“…The persistence of these ancient and diverged lineages in the Indian subcontinent may be due in part to the region’s unique topography and paleoenvironmental history. Similar patterns of locally divergent lineages have been observed in Trans-Himalayan red pandas ( Hu et al 2020 ) and Chinese mountain cats ( Yu et al 2021 ). Together, these findings point to the importance of the Indian subcontinent and Trans-Himalayan region as refugia during the Pleistocene ( Sharma et al 2004 ; Costa 2017 ) that enabled the persistence of divergent lineages.…”
Section: Discussionsupporting
confidence: 71%
“…Previous studies have showed genetic introgression of wild relatives in domestic animals such as sheep, goat, pig, dog, cattle, yak, cattle, rabbit, horse, and chicken ( Ai et al 2015 ; Medugorac et al 2017 ; Jones et al 2018 ; Wu et al 2018 ; Lawal et al 2020 ; Wang et al 2020 ; Zheng et al 2020 ; Cao et al 2021 ; Yu et al 2021 ; ). The proportion of wild introgression varies from 0.05% to 27.3% depending on the populations of domestic animals and the relevant wild relatives ( supplementary table S48, Supplementary Material online).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of Chinese random-bred cats and the local wildcat species/subspecies ( F.s. bieti ) suggest the noted introgression of this wildcat with random-bred cats in China does not explain the distinctive genetics of Far Eastern and Western European random-bred cats; further, the agricultural center near the middle Yangtze and Yellow Rivers is likely not a second domestication site for cats (Yu et al 2021 ). While these previous studies all support the domesticated F.s.…”
Section: Introductionmentioning
confidence: 99%